Tidlig algebra - Petersen, Tina Otykier; Mortensen, Ulla Christina (MONA - Matematik- og Naturfagsdidaktik, 2011)
Med udgangspunkt i et empirisk studie i en 2.-klasse undersøger vi hvordan aspekter afalgebra og algebraisk tænkning er mulige at indføre allerede tidligt i elevernes skolegang. At flytteden traditionelle algebraundervisning ned i indskolingen fører i sig selv ikke til at eleverne bliver bedretil algebra og til at tænke algebraisk. Det drejer sig derimod om at tænke i nye baner og indføre tidligalgebra. Forholdet mellem algebra og aritmetik (regning) bør revurderes. Algebra skal ikke ses somefterfølger til aritmetik, men aritmetik bør derimod ses som en del af algebra. Based on an empirical study in a second grade, we investigate how aspects of algebra and algebraicthinking are possible to introduce in an early stage of the students’ education. Repositioning the teachingin traditional algebra to the introductory years of the elementary school does not itself improvestudents’ algebraic skills or their algebraic thinking. One should rather promote innovation that comeswith the introduction of Early Algebra. The relationship between algebra and arithmetic should bereconsidered. Algebra should not be viewed as a successor to arithmetic; on the contrary, arithmeticshould be seen as a subset of algebra.